THE CONTRIBUTION OF INFORMAL TRADING TO TOURISM DEVELOPMENT- THE CASE STUDY OF TSHAKUMA FRUIT MARKET, LIMPOPO, SOUTH AFRICA - Mokabe, Mamotse; Tshifularo, Mpho (PEOPLE: International Journal of Social Sciences, 2018)
Since 1994 the informal trading sector has been growing in South Africa. Though defined as informal, and remaining largely unregulated, the sector has played, and continues to play, a significant role in creating jobs and enhancing the spirit of entrepreneurship in our country, besides helping many citizens to be financially self-reliant. The case study focuses on informal traders in the Tshakuma fruit market in Limpopo Province, South Africa, the main objective being to explore the nature and extent of the contribution of these traders to the development of tourism in the Venda District Municipality (VDM). The location of this market was considered of particular interest as a setting, not only because of Government’s recent R 4.85 million intervention to boost economic growth in the area, but also because it is on the main tourist route to a primary national and international tourist attraction: the Kruger National Park. The study employed a quantitative research method using questionnaires distributed to both traders and tourists and a thematic content data analysis. Study found tourism in the VDM to have expanded significantly in recent years particularly in the vicinity of the market. The findings indicate both the potential both for the informal trading market to be a pulling factor for the Kruger National Park and other tourist attractions in the area, and also to address the high rates of employment and insufficient incomes associated with poverty in our country.